Intimate Partner Violence and Use of Primary and Emergency Care: The Role of Informal Social Support - Dias, NG (2020)
Social support may encourage victims to disclose their experiences of intimate partner violence (IPV), but also to seek the appropriate help and care in the social and health services. Using data from a multicenter European project, DOVE (Domestic Violence Against women/men in Europe—prevalence, determinants, effects, and policies/practices), the present study aimed at measuring the frequency of primary care and emergency use according to IPV types of victimization, and to investigate whether victims receiving different levels of informal social support are using health care differently. Results suggested a significant association between IPV types and use of emergency services, and no association was found regarding primary care services. Victims of physical abuse and sexual coercion went to the emergency department (ED) more frequently (more than once a year). Also, victims of physical abuse receiving low social support visited an ED more frequently than those with high social support, whereas victims of sexual coercion with high informal social support went more often to the ED compared with victims of sexual coercion with low social support, even after controlling for other covariates. These results seem to suggest that social support has a significant role in the decision to use health care among victims of IPV.